Pengaruh Pelayanan m-Banking Terhadap Kepuasan Nasabah Pada Bank Syariah Mandiri Kota Prabumulih - Zakaria Harahap (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
The purpose of this study was to determine the effect of m-Banking on customer satisfaction at Bank Syariah Mandiri in Prabumulih City. This type of research is a survey research with quantitative descriptive approach. The population is all customers at Bank Syariah Mandiri in Prabumulih City, samples were taken by 90 respondents, using random sampling technique with saturated sample method. This study uses primary data obtained from respondents' answers in the form of questionnaire filling, that is, data obtained directly from the research object. Data analysis techniques include: the test instrument consists of validity and reliability tests, the classic assumption test consists of tests of normality, multicollinearity, and heteroscedasticity, simple linear regression test and hypothesis test consisting of the F test, test the coefficient of determination and t test. The results of the study for the determination test show R Square of 0.738. shows that the value of R Squre (coefficient of determination) is 0.738. This means that the m-Banking service variable on Customer Satisfaction is 73.8% while the remaining 26% (100% - 73.8 = 26.2%) is influenced by other factors outside the study.